2020
DOI: 10.1038/s41467-020-19133-w
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic capture of a low-spin Mn(IV)-oxo species in Ni–Mn3O4 nanoparticles during water oxidation catalysis

Abstract: High-valent metal-oxo moieties have been implicated as key intermediates preceding various oxidation processes. The critical O–O bond formation step in the Kok cycle that is presumed to generate molecular oxygen occurs through the high-valent Mn-oxo species of the water oxidation complex, i.e., the Mn4Ca cluster in photosystem II. Here, we report the spectroscopic characterization of new intermediates during the water oxidation reaction of manganese-based heterogeneous catalysts and assign them as low-spin Mn(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 60 publications
1
12
1
Order By: Relevance
“…Very recently, an unprecedented signal at g ∼ 1.8 was observed during water oxidation reactions involving manganese-containing heterogeneous catalysts; the feature was assigned to a low-spin Mn( iv )-oxo species with S = 1/2. 95 Although the signal at ∼2 described in the present work could be also generally ascribed to a low-spin Mn( iv )-oxo species, we could not adequately fit the data using a S = 1/2 model; a S = 3/2 model provides a superior fit.…”
Section: Resultscontrasting
confidence: 57%
“…Very recently, an unprecedented signal at g ∼ 1.8 was observed during water oxidation reactions involving manganese-containing heterogeneous catalysts; the feature was assigned to a low-spin Mn( iv )-oxo species with S = 1/2. 95 Although the signal at ∼2 described in the present work could be also generally ascribed to a low-spin Mn( iv )-oxo species, we could not adequately fit the data using a S = 1/2 model; a S = 3/2 model provides a superior fit.…”
Section: Resultscontrasting
confidence: 57%
“…Park et al reported that surface Ni-doping on Mn 3 O 4 introduced high-valent Mn 4+ states. The Ni-doped Mn 3 O 4 catalyst exhibited excellent ORR activity because the adsorption of O 2 , which is recognized as the rate-limiting step for the ORR, has an optimum strength on Mn­(IV) cations (Mn 4+ –O 2 ) for better ORR activity . However, these Mn-based oxides usually show limited OER activity .…”
Section: Introductionmentioning
confidence: 99%
“…The Nidoped Mn 3 O 4 catalyst exhibited excellent ORR activity because the adsorption of O 2 , which is recognized as the rate-limiting step for the ORR, has an optimum strength on Mn(IV) cations (Mn 4+ −O 2 ) for better ORR activity. 40 However, these Mn-based oxides usually show limited OER activity. 41 Previous works suggested that Ni 3+ -based oxides with strong Ni 3d−O 2p hybridization are efficient OER electrocatalysts.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Reprinted with permission from Park et al. 14 Copyright 2020 Springer Nature. (C and D) Depictions of how the dopant atom added to the base material in both cases yields EPR-visible paramagnetic species Ni 3+ and low-spin Mn 4+ .…”
Section: Examination Of Mixed Metal Catalysts – Mn-ni O 2 ...mentioning
confidence: 99%
“…Alternatively, Ni doping into spinel Mn 3 O 4 nanoparticles also can result in a more active Mn-Ni oxide OER catalyst. 14 By tracing the behavior of the catalyst on polarization using ex situ freeze-quenching, it was observed that a new, low-spin Mn 4+ species was found to emerge, leading the authors to conclude that Ni stabilized low-spin Mn 4+ in Mn 3 O 4 within a compressed crystal field ( Figures 6 B and 6D). Notably, at no time were any EPR spectra for Ni 3+ observed, demonstrating that the oxidation state of Ni remained Ni 2+ .…”
Section: Examination Of Mixed Metal Catalysts – Mn-ni O 2 ...mentioning
confidence: 99%